Un ufficio inedito per s. Anna - Brusa, Gionata (Scrineum, 2013)
The article deals with the office of St. Anna, mother of the Blessed Virgin in Vercelli. His first mention is in the Liber Ordinarius Vercelli, Biblioteca Capitolare, LIII written in the 1372 for the Cathedral. Unfortunately the office, in his solemn form provided with 9 lessons, as described in the Liber Ordinarius, survives in only one manuscript: the Antiphonary Vercelli, Biblioteca Capitolare, LXXIX (first half of the 13th cent.).